LOS LINFOCITOS EN LA FORMULA LEUCOCITARIA ENSAYO SOBRE LA PREPARACION DE FROTES - MOREIRA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1940)
The author shows that the usual way of making smears (placing a drop of blood at one end of a slide, and using a second slide to a drop of blood at one end of a slide, and using a second slide to a drop of blood at one end of a slide, and using a second
REV MEX MED
Keywords: LINFOCITOS, FORMULA, LEUCOCITARIA, ENSAYO, PREPARACION, FROTES; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOGIA CLINICA